Analysis and Design of Natural Spring Water Preservation and Monitoring System Using Rapid Application Development - Singgalen, Yerik Afrianto (Journal of Information System and Informatics, 2024)
Climate change in Indonesia has resulted in droughts in several regions, affecting both ecological conditions and the livelihoods of local communities in accessing clean water sources. Therefore, natural spring water preservation and monitoring are needed to identify and analyze the factors contributing to ecological changes. This research utilizes the Rapid Application Development method through the Oracle Apex instrument in designing the database and information system for natural spring water preservation and monitoring. The stages of designing this application are requirements planning, user design, construction, and cutover. Each stage has its challenges, namely the relevance of data to user needs in identifying and analyzing the sustainability of natural spring waters. The findings of this study demonstrate that information on natural spring water location, water quality, local community activities, and observer data play a crucial role in the decision-making process. Through this application, natural spring waters can be identified and protected through appropriate policies, thus contributing to Indonesia's sustainable water resource management and environmental conservation efforts. Additionally, the analysis and design results reveal insights into the structural framework and functionalities of the developed system, highlighting its potential to effectively address the complexities of natural spring water preservation and monitoring.